2012
DOI: 10.1039/c1mt00147g
|View full text |Cite
|
Sign up to set email alerts
|

DNA binding and nucleolytic properties of Cu(ii) complexes of salicylaldehyde semicarbazones

Abstract: The copper(ii) complexes of two salicylaldehyde semicarbazones, HOC(6)H(4)CH[double bond, length as m-dash]N-NHCONR(2) [H(2)Bnz(2) (R = CH(2)Ph) and H(2)Bu(2) (R = Bu)], were evaluated for their DNA binding and cleavage properties by spectrophotometric DNA titration, ethidium bromide displacement assay and electrophoretic mobility shift assay. Results showed that the Cu(ii) complexes can bind to DNA via a partial intercalation mode with binding constants of 1.1 × 10(4) and 9.5 × 10(3) M(-1) for [Cu(HBnz(2))Cl]… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(9 citation statements)
references
References 57 publications
1
8
0
Order By: Relevance
“…However, a gradual quenching of the EB‐DNA emissive intensity can occur in presence of a strong intercalator, which is capable of replacing DNA‐bound EB and/or can accept the excited state electron from EB. [ 37 ] In our experiments, upon progressive addition of increasing concentration of the complex 1 (0.0–0.55 × 10 −5 M) to a fixed concentration of DNA‐EB system, a prominent decrease in fluorescent intensity at λ max = 580 nm was noticed, which validated the intercalating mode of binding (Figure S6). We have further calculated the apparent binding constant K app by using the equation.…”
Section: Resultssupporting
confidence: 72%
“…However, a gradual quenching of the EB‐DNA emissive intensity can occur in presence of a strong intercalator, which is capable of replacing DNA‐bound EB and/or can accept the excited state electron from EB. [ 37 ] In our experiments, upon progressive addition of increasing concentration of the complex 1 (0.0–0.55 × 10 −5 M) to a fixed concentration of DNA‐EB system, a prominent decrease in fluorescent intensity at λ max = 580 nm was noticed, which validated the intercalating mode of binding (Figure S6). We have further calculated the apparent binding constant K app by using the equation.…”
Section: Resultssupporting
confidence: 72%
“…Cu(II) complexes of terminally N-substituted SSC showed considerably higher antiproliferative activity than their respective ligands triggering apoptotic cell death [9]. Binding of these Cu(II) complexes to DNA via partial intercalation with a subsequent cleavage of DNA via generation of hydroxyl radicals was also proved, which is most probably in a strong relation to their anticancer property [10]. V(V) complexes formed with N 4 -(2-naphthyl)semicarbazone were also reported for their selective potency on human kidney tumour cells [13−15].…”
Section: Introductionmentioning
confidence: 92%
“…Since metal complexes with no extended planar rings are not expected to displace the intercalatively bound EB, small reduction of DNA-EB uorescence intensity indicates that quenching occurs by photo electron-transfer mechanism. [76][77][78] Previous investigation on a series of Cu(II) complexes indicated that the ability of the complexes to quench the EB emission intensity by photo electron-transfer mechanism depends upon their reducibility: the complex with a more positive redox potential (À0.219 V) had the highest ability to quench the emission intensity of EB. Redox potential of 1 is even more positive, which indicates its capability to undergo photo electron-transfer mechanism.…”
Section: Fluorescence Quenching Studiesmentioning
confidence: 99%